A Dynamic Model of Optimal Capital Structure - Titman, Sheridan; Tsyplakov, Sergey (Review of Finance, 2007)
Abstract This paper presents a continuous time model of a firm that can dynamically adjust both its capital structure and its investment choices. In the model we endogenize the investment choice as well as firm value, which are both determined by an exogenous price process that describes the firm's product market. Within the context of this model we explore cross-sectional as well as time-series variation in debt ratios. We pay particular attention to interactions between financial distress costs and debtholder/equityholder agency problems and examine how the ability to dynamically adjust the debt ratio affects the deviation of actual debt ratios from their targets. Regressions estimated on simulated data generated by our model are roughly consistent with actual regressions estimated in the empirical literature.